Confined fluidization of fines in fixed bed of coarse particles - Buczek Bronisław; Zabierowski Piotr (Chemical and Process Engineering)
Experiments on a confined fluidized bed system with various shapes of particles have been presented in the paper. Its influence on hydrodynamic properties in the whole range of gas velocity has been analysed. Relations allowing calculation of the Richardson-Zaki-type equation coefficients, including description of inter-particle void and gas pressure drop in such systems have been determined. Necessary condition for confined fluidization of non-spherical coarse particles has also been determined.